(untitled) (The Research of Medical Science Review, 2024)
The present study was to explore dragonfly fauna in the District Dera islamil khan Khyber Pakhtunkhwa Pakistan. Duration of this study is 9 months i.e. February 2021 to November 2021. A total of 915 specimens were collected from the sampling site, Paharpur, Daraban, Kulachi, Prova and main Dikhan city of the district Dikhan. The identified specimens belongs to order Odonata 2 families Libellulidae and Aeshnidae,8 genera and 14 species respectively. Family Libellulidae was the largest family consisting 13 species Palpopleura sexmaculata, pantala flavescense, Orthetrum chrysis, Orthetrum cancellatum cancellatum, Orthetrum Sabina, Orthetrum gluacum luzonicum, Bradinopyga germinata and trithemis festiva. Family Aeshnidae comprising only one specie Anax Immaculifrons it can be concluded that this region have a diverse dragonfly fauna. Similarly survey on large scale is recommended to fully evaluate the dragonfly fauna of District Dera Ismail khan kpk Pakistan.